Predicting Acute Ischaemic Stroke Outcome Using Clinical and Temporal Thresholds. (6th September 2011) - Sablot, Denis; Belahsen, Faouzi; Vuillier, Fabrice; Cassarini, Jean-François; Decavel, Pierre; Tatu, Laurent; Moulin, Thierry; Medeiros de Bustos, Elisabeth
Abstract : Background. Few studies have analysed the natural course of cerebral ischaemia for predicting outcome. We aimed to determine the early clinical findings and the thresholds for deficit severity and symptom duration that make it possible to stratify outcome. Methods. We included 154 patients with transient ischaemic attack or ischaemic stroke. Stroke profiles and neurological status were assessed from onset to 24 hrs, on admission, at 48 hrs, and at discharge. Outcomes were evaluated using the modified Rankin Scale. Positive and negative predictive values were calculated for the different thresholds. The model was subsequently evaluated on a new prospective cohort of 157 patients. Results. Initial National Institute of Health Stroke Scale (NIHSS) score <5 and symptoms regressing within 135 min were predictive of good outcome. Initial NIHSS score >22 and symptom stability after 1, 230 min were predictive of physical dependency or death. Conclusions. Low and high NIHSS cut-off points are effective positive predictive values for good and poor outcomes. Thresholds for symptom duration are less conclusive.